Prehabilitation for Frail Patients Undergoing Colorectal Surgery: Lessons Learnt From a Randomised Feasibility Study - Furyk, Claire; Senthuran, Siva; Nye, Dia; Ho, Yik H.; Leicht, Anthony S. (Frontiers in Rehabilitation Sciences, 2021)
There is substantial interest by clinicians to improve the health outcomes of older and frail patients following major surgery, with prehabilitation a potential and important component of future standard patient care. We studied the feasibility of a randomised controlled trial of pre-operative prehabilitation in frail patients scheduled for colorectal surgery in regional Australia. We conducted a single blind, parallel arm, randomised controlled trial in a regional referral centre where colorectal surgical patients aged over 50 were invited to participate and screened for frailty. Frail patients were randomised to undertake either a 4-week supervised exercise program with dietary advice, or usual care. The primary outcome was 6-min-walk-distance at baseline, pre-surgery (4 weeks later) and at follow-up (4–6 weeks post-operation). Secondary outcomes included physical activity level, health-related quality of life, and post-surgical complications. Feasibility outcomes were numbers of patients reaching each stage and barriers or reasons for withdrawal. Of 106 patients eligible for screening during the 2-year study period, only five were able to be randomised, of which one alone completed the entire study to follow-up. Fewer patients than expected met the frailty criteria (23.6%), and many (22.6%) were offered surgery in a shorter timeframe than the required 4 weeks. Physical and psychological aspects of frailty and logistical issues were key for patients declining study participation and/or not complying with the intervention and/or all outcome assessments. Feasibility for a large randomised controlled trial of prehabilitation for frail colorectal patients was poor ( 5%) for our regional location. Addressing barriers, examination of a large, dense population base, and utilisation of a frailty-screening tool validated in surgical patients are necessary for future studies to identify the impact of prehabilitation for frail patients.